ANALISIS YURIDIS PERLINDUNGAN HUKUM RUMAH SAKIT TERHADAP TANGGUNG JAWAB ATAS PENOLAKAN PENGOBATAN PASIEN BERDASARKAN PASAL 192 UU NO. 17 TAHUN 2023 - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to analyse, from a legal perspective, the legal protection afforded to hospitals regarding their responsibility to refuse treatment to patients based on Article 192 of Law No. 17 of 2023 on Health Services. Refusal of treatment by hospitals is often a source of complex legal conflicts, necessitating a clear legal framework to protect hospitals while guaranteeing patients' rights. The research method used is normative legal with a qualitative approach through a review of documents and related legal literature. The results of the analysis show that Article 192 provides a strong legal basis for hospitals to refuse treatment legally and procedurally, with measurable and limited responsibilities in accordance with the provisions of the law. The legal protection regulated by this provision is able to maintain the professionalism of hospitals while ensuring that patients' rights are not neglected. This research has important implications for the development of health law policies that are fair and oriented towards the protection of all parties.